Histoplasmosis A Comprehensive Study of Epidemiology, Pathogenesis, Diagnosis, and Treatment - Dantes, Elena; Dumea, Elena (Infectious Diseases, 2023)
The true incidence of histoplasmosis remains difficult to ascertain due to the lack of mandatory notification of the disease, resulting in an underestimation of its actual burden. Given the high mortality rate, especially for disseminated forms in immunocompromised patients, we must remain vigilant against fungal disease. This book, born out of a deep desire to expand our knowledge of this fungal disease and update the latest findings, is intended to assist clinicians in recognizing and effectively managing histoplasmosis, especially those who live outside endemic areas and are less familiar with this pathology. With the latest insights into epidemiology, pathophysiology, clinical manifestations, and diagnostic approaches for both immunocompetent and immunodeficient patients, this comprehensive volume provides infectious disease specialists, pulmonologists, and laboratory physicians with the tools they need to optimize the management of histoplasmosis.